PID Control for Experimental Flexible Inverted Pendulum - Minh-Tam Nguyen; Van-Dong-Hai Nguyen (Robotica & Management, 2020)
Flexible inverted pendulum is distributed parameter SIMO system which is developed from cart and pole, a popular robot with all solid links. A structure of PID controller for this model is suggested. Approximated dynamic equations of this model is used to obtain the PID controller by genetic algorithm through simulation. After survey in simulation, a hardware platform is presented and tested. In experiment, PID is proven to work well and suit most theoretical points.